Strategic Priorities in Agriculture - Berdiyev A. H; Rasulov Kh. K. (Research Parks Publishers, 2021)
In this article the main strategic priorities in the sector of agriculture explained. Agriculture has been considered as a key to stabilize the economies in the context of coronavirus pandemic, especially in Central Asia. As well as, the role of agriculture in the economy of Uzbekistan analyzed. and the importance of approved Strategy for the Development of Agriculture of Uzbekistan for 2020-2030 explained.